Rituximab and reduced‐intensity chemotherapy in children and adolescents with mature B‐cell lymphoma: interim results for 231 patients enrolled in the second Russian‐Belorussian multicentre study B‐NHL‐2010M. (9th May 2019) - Maschan, Alexey; Myakova, Natalia; Aleinikova, Olga; Abugova, Yulia; Ponomareva, Natalia; Belogurova, Margarita; Fechina, Larisa; Fedorova, Alina; Grigor'eva, Natalia; Lebedev, Vladimir; Nikonova, Olga; Shamardina, Anastassia; et al.
Summary: The value of adding rituximab to chemotherapy in children with aggressive B‐cell non‐Hodgkin lymphoma (B‐NHL) is still insufficiently studied. We enrolled 231 patients [mean age 9 years old (range 2–17); male:female ratio 3·4:1] with Burkitt (BL, 179 patients, 76·7%), diffuse large B‐cell (32 patients, 14%), primary mediastinal B‐cell (14 patients, 6%), and other (6 patients, 2·6%) B‐cell lymphomas in a prospective study of immuno‐chemotherapy. Stages were I–II in 32% and III–IV in 68% of the patients. Four doses of 375 mg/m 2 rituximab were added to the Berlin‐Frankfurt‐Munster‐NHL‐90‐like chemotherapy, with methotrexate being reduced or omitted in the first 2 induction blocks. The complete remission rate was 100% in limited‐stage and 91·4% in advanced‐stage patients. Five advanced‐stage patients (2·2%) died in induction and 1 patient with stage 2 B‐NHL died in remission; 11 patients in the high‐risk group progressed on therapy (3 non‐BL are alive after salvage) and 5 relapsed. Sixteen patients (9·7%) with advanced stage disease proceeded to transplant. With a median follow‐up of 46 months, 98·5 ± 1% of patients with limited disease and 88·1 ± 2% (88·1% in Risk Group 3; 82·6% in Risk Group 4) in advanced stages are alive. This study confirmed that combined immunochemotherapy for B‐lymphomas is highly effective in children, despite reducing the intensity of the induction blocks.